The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.21608/jcese.2022.270143
|View full text |Cite
|
Sign up to set email alerts
|

Topp-Leone Weibull Generated Family of Distributions with Applications

Abstract: We reveal and investigate the Topp-Leone (TL) Weibull G (TLWG) family, a new generator of continuous lifespan distributions, as a consequence of this article. However, various of its statistical characteristics have been proposed. Examine the TLWG family, a new source of continuous lifespan distributions. The parameters of maximum likelihood (MLL) estimations are predicted. We can see the significance and versatility of the recommended family of algorithms while using the TLW exponential model as an example of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…For more information about simulation study see [10], [11], and [12]. Hence, we assess the performance of the MLE using correct initial values and an obvious algorithm as follows:…”
Section: Simulationmentioning
confidence: 99%
“…For more information about simulation study see [10], [11], and [12]. Hence, we assess the performance of the MLE using correct initial values and an obvious algorithm as follows:…”
Section: Simulationmentioning
confidence: 99%
“…In 2021, Mahmood et al [19] published an enlarged Cosine generalised family of distributions for dependability modelling: characteristics and applications with simulation analysis, and Muse et al [20] suggested a new flexible form of the loglogistic distribution. Citations [5], [17], and [6] in 2022 explored a family of produced distributions with applications.…”
Section: Introductionmentioning
confidence: 99%
“…The recurrence relations (RRs) for moments of DGOS for exponentiated Weibull model have been investigated by [7] whereas the relations for moments of power function model was investigated by [8]. Topp-Leone Weibull generated family of distributions with applications was found in [19]. The RRs for moments of DGOS for a inverted Kumaraswamy model was found in [9].…”
Section: Introductionmentioning
confidence: 99%